Cannabinoid Use Among Liver Transplant Recipients. Issue 11 (20th July 2021) - Yan, Kathleen; Forman, Lisa
Abstract : The effect of cannabinoids on liver transplant outcomes is an area of active research. We aimed to investigate marijuana (MJ) and cannabidiol (CBD) use among liver transplant recipients at the University of Colorado Hospital (UCH), specifically prevalence, habits, and predictors of use. Liver transplant recipients followed at UCH with valid email addresses were sent an informed consent postcard and survey invitation. This exploratory survey was conducted using REDCap. IBM SPSS Statistics software was used for statistical analysis. Of 1227 recipients who were sent surveys, 538 people responded. On average, respondents were 59 years old, with 63.7% male and 81.7% White. Hepatitis C virus (HCV; 30.4%) and alcohol use (17.7%) were the most common etiologies of liver disease. Among respondents, 23.8% reported current MJ use. Methods of use included smoking (72.4%), ingestion (55.3%), and vaporization (31.7%). Top reasons for MJ use were recreation (56.5%), anxiety (54.8%), and pain (53.2%). Among respondents, 21.0% currently used CBD, usually in the form of creams or lotions (58.9%) and to relieve pain (84.9%) and anxiety (31.1%). In multivariable analysis, age (odds ratio [OR], 0.941; 95% confidence interval [CI], 0.923‐0.959; P < 0.001), diabetes mellitus (OR, 0.357; 95% CI, 0.171‐0.746; P = 0.01), HCV cirrhosis (OR, 3.949; 95% CI, 2.281‐6.835; P < 0.001), alcohol‐related cirrhosis (OR, 2.101; 95% CI, 1.202‐3.671; P = 0.01), and current tobacco use (OR, 2.918; 95% CI, 1.065‐7.990; P = 0.04) were significant predictors of MJ use. Our study shows that cannabinoid use after liver transplant is common. MJ use is associated with decreasing age, alcohol‐related and HCV cirrhosis, and tobacco use. Anxiety, pain, and recreation were top reasons for its use. Transplant teams should address reasons why their patients use MJ and CBD and develop programs to mitigate anxiety and pain after transplant. Further studies are needed to examine effects of cannabinoids on liver transplant outcomes.